St Augustine’s Teaching on the Image of God in Man in the Mystery of Creation - Kołacz, Piotr (Studia Theologica Varsaviensia, 2020)
ree comments on the Book of Genesis and the treatise On the Trinity enabled us to become acquainted with the Augustinian teaching on the image of God in man in the mystery of Creation. anks to such a narrowing of the source material, we could more carefully and with greater prudence analyze the thoughts of the Bishop of Hippo. We hope that in this way we managed to avoid the risk of superficiality and we took into account all the statements of Saint Augustine regarding the problem posed. Unfortunately, L. Krupa did not prevent himself from committing this mistakeN8. He did not take up the subject of human nature as an image of God, and completely passed over in silence the polemics of the Bishop of Hippo with Gnostics, who regarded the human family as the image of the Holy Trinity. Based on the analysis carried out, we could see that according to Saint Augustine’s image of God in man is to be sought in his soul, and in the strict sense, in this “part” of him, which is focused on the contemplation of eternal ideas. e essence of the image of God is expressed in the ability of the soul to participate in God’s life. All this reflects, as Saint Augustine states, the true honour and dignity which man owes to his Creator. A characteristic feature of God’s image, even a basic one – in view of the Augustinian approach – is its trinitarian character. Saint Augustine tried to seek the traces of the Holy Trinity everywhere. is significant task was the passion of his life. Finally, he has found the image of the Holy Trinity in man. He tried to provide his readers with an insight into this reality through the trinitarian analogies, the source of which he discovered in the structure of the human soul. Considering the entirety of St. Augustine’s teaching on the image of God in man in the mystery of Creation, the analogous images of the Holy Trinity in the soul seem to be the most interesting for us. On the other hand, like Saint Augustine, however, we are aware of their great limitations. For what is created, even in its most beautiful representation, in comparison with the Creator will always be in a vulnerable and poor condition.